2020
DOI: 10.1002/aet2.10541
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Treasure Hunt: A Novel Teaching Method That Overcomes Direct Patient Care Restrictions Brought on by the COVID‐19 Pandemic

Abstract: Prioritizing trainee safety during the COVID‐19 era is paramount. In March 2020, the AAMC recommended prohibiting medical students from direct patient care in significantly affected regions. Guidelines continue evolving; however, the AMA continues to recommend clinical experiences, not requiring direct patient care, be achieved through virtual formats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Figure 2(e) graphically presents the range of included learners amongst the 48 studies which presented a precise number of participants. The mean number of participants was 53.7 and the range was 2 (Bautista et al 2020;Shibata et al 2020) to 610 (Trujillo et al 2020). Seven studies did not provide the number of participants.…”
Section: Number Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2(e) graphically presents the range of included learners amongst the 48 studies which presented a precise number of participants. The mean number of participants was 53.7 and the range was 2 (Bautista et al 2020;Shibata et al 2020) to 610 (Trujillo et al 2020). Seven studies did not provide the number of participants.…”
Section: Number Of Participantsmentioning
confidence: 99%
“…The authors found that for the educational task of corneal suturing, the use of a remote wet lab was as effective as previous in-person wet labs. Shibata et al (2020) described an 'Ultrasound Treasure Hunt,' where novice learners performed ultrasonography on themselves and the people they were in direct with, against step-by-step instructions and a 'treasure map.' Image files were then uploaded for faculty to view, where feedback was provided using video conferencing software with screen sharing functionality.…”
Section: Remote Laboratoriesmentioning
confidence: 99%